2019
DOI: 10.1108/jima-11-2017-0123
|View full text |Cite
|
Sign up to set email alerts
|

The role of Islamic marketing ethics towards customer satisfaction

Abstract: Purpose Islamic marketing ethics focus on the principles of equity, justice and value maximization for the welfare of society. These ethics play a vital role in elevating the standards of customer behavior. The strategy of focusing customer is now considered as important element because of rapidly changing marketing trends in Islamic banks. Therefore, the purpose of this study is to find out the important features of Islamic marketing ethics and identify their effect on customer’s satisfaction in Islamic banki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 34 publications
2
58
0
12
Order By: Relevance
“…(2018) identified that eight moral factors of ethical conducts were common to all of those major six religions: assurance, fairness/honesty, charity/compassion, environment, tolerance, character/integrity, sacrifice and seriousness. The discussions of IM ethics covers almost all areas of marketing; from marketing mix, marketing communications, branding, consumer behaviour, retailing to international marketing (Abbas et al., 2019; Al‐Nashmi & Almamary, 2017; Arham, 2010; Aziz, 2018; Karami et al., 2014; Saeed et al., 2001; Souiden et al., 2018; Turnbull et al., 2016; Uysal & Okumuş, 2019; Yousaf, 2014).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018) identified that eight moral factors of ethical conducts were common to all of those major six religions: assurance, fairness/honesty, charity/compassion, environment, tolerance, character/integrity, sacrifice and seriousness. The discussions of IM ethics covers almost all areas of marketing; from marketing mix, marketing communications, branding, consumer behaviour, retailing to international marketing (Abbas et al., 2019; Al‐Nashmi & Almamary, 2017; Arham, 2010; Aziz, 2018; Karami et al., 2014; Saeed et al., 2001; Souiden et al., 2018; Turnbull et al., 2016; Uysal & Okumuş, 2019; Yousaf, 2014).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Abbas et al. (2019) defined IM as ‘ The process and strategy of fulfilling need through halal products and services with the mutual consent and welfare of both parties (i.e., buyers and sellers) for the purpose of achieving material and spiritual wellbeing in the world here and the hereafter ’. Wilson (2012) defined IM as ‘ a school of thought which has a moral compass which tends towards the ethical norms and values of Islam and how Muslims interpret these, from their varying cultural lenses ’.…”
Section: Introductionmentioning
confidence: 99%
“…Prinsip etika dalam Islam memberikan arahan bagi seorang Muslim tentang cara menjalani hidup dengan lebih bermakna dan bermanfaat. (Abbas et al, 2019) menyebutkan bahwa etika pemasaran Islam berbeda dengan etika sekuler karena berlandaskan prinsip Islam yang menjunjung nilai persamaan dan keadilan. Etika pemasaran Islam menjamin segala kepentingan pihak terkait meliputi transaksi, pembeli, penjual, mitra bisnis, komunitas dan sebagainya.…”
Section: Kajian Literatur Etika Pemasaran Islam (Islamic Marketing Ethics)unclassified
“…Etika pemasaran Islam juga memiliki tiga karakteristik dasar berkaitan dengan refleksi prinsip Al-Qur'an berupa ketiadaan monopoli oleh para eksekutif bisnis yang berpotensi menimbulkan kesewenangan, bersifat absolut dan non-fleksibel (tidak ada kesempatan penawaran yang dapat menimbulkan moral hazard), serta maksimalisasi nilai yang tidak hanya mengejar keegoisan keuntungan semata (Abbas et al, 2019). Oleh karena itu, Islam merupakan agama yang inti dasarnya berkaitan erat dengan nilai moralitas.…”
Section: Kajian Literatur Etika Pemasaran Islam (Islamic Marketing Ethics)unclassified
See 1 more Smart Citation